ANESTESIA EM FELINO PARA CORREÇÃO DE HÉRNIA DIAFRAGMÁTICA: RELATO DE CASO - DA SILVA, TAIZA; Moreira Silva, Ana Clara; Rodrigues Barbosa Ferreira, Ana Flávia; da Silva Gonçalves, Larissa; Ferreira de Oliveira, Nayara Cristina; Barboza Alves, Karoline; Antunes de Lima, Marcos Paulo; Aparecida Moura, Luciana (Sinapse Múltipla, 2023)
Não se aplica